Non-contact sensing-actuating composite material and preparation method thereof
By adopting the triple effect of dielectric polarization-electric thermal conversion-thermal response actuation in intelligent materials, logical perception and flexible actuation of the three-dimensional motion of non-contact objects are achieved, solving the complex problems of sensing and actuation function separation and energy conversion, and achieving efficient and low-power non-contact sensing-actuation integration.
Patent Information
- Application Number
- CN202411810912.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-10
AI Technical Summary
When sensing external environmental information, existing smart materials often stay on the surface of the 2D skin, which leads to inevitable contact damage and power consumption, and cannot obtain external environmental information in full; at the same time, existing non-contact sensing materials have a single sensing function, which cannot achieve logical perception of the direction and speed of external objects; and, in addition, the driving voltage of the electrical/electrothermal drive flexible actuator materials is high, which is not conducive to safe interaction and energy conservation and emission reduction.
A non-contact sensing-activating composite material based on the triple effect of "dielectric polarization-electrothermal conversion-thermal response actuation" is adopted. It has a nano-scale multi-layer network structure. Through the electrostatic field and its polarization effect on the dielectric material, it generates logical perception of the three-dimensional motion of non-contact objects in the environment, and drives the electric thermal effect of the silver nanowire layer through the sensing signal to achieve flexible actuation.
The logical perception of the three-dimensional motion of non-contact objects in the outside world is realized. The perception distance can reach 20cm, the actuation time is less than 1s, the shape memory reply rate is greater than 95%, and the driving voltage is reduced to 2V and the response speed is less than 1s, which solves the complex problems of sensing and actuation functions separation and energy conversion.
Smart Images

Figure CN119803266A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sensing and actuating materials, and in particular to a non-contact sensing-actuating composite material and a preparation method thereof. Background Art
[0002] With the development of artificial intelligence, in addition to simply receiving instructions to produce mechanical deformation, soft actuators need to more intelligently perceive external environmental information and make corresponding action feedback, imitating the human sensory-motor system [Nat. Rev. Neurosci. 201112(3):139-153]. Therefore, the design of smart materials needs to integrate sensing and actuation characteristics. Among them, there are two types of sensing methods: proprioception of self-deformation and environmental perception of external information [Science 2015,347(6228):12616891].
[0003] Research has been reported on the proprioception of materials' own deformation and controlling their actuation to form closed-loop control. Hao et al. designed an electrothermal actuator based on laser-induced graphene (LIG) and self-sensed its deformation state through the resistance change of LIG, but its driving voltage was 20V to achieve the required bending angle and number of cycles [ACSAppl.Mater.Interfaces 2022,14,41283-41295]. Wang proposed a light-driven mini flexible robot with proprioception. The robot is composed of a multilayer structure of conductive graphite-carbon nanotube composites, ferroelectric polyvinylidene fluoride (PVDF), photothermal polydopamine (PDG), and reduced graphene oxide. PVDF and PDG with opposite thermal expansion coefficients constitute a double-layer actuator. Its temperature change and driving strain are respectively fed back through the inherent pyroelectricity of PVDF and the piezoresistivity of the graphite-carbon nanotube circuit, but multiple sensor signals are prone to crosstalk with each other [Adv. Mater. 2020, 32, 2000351]. Lo et al. designed a self-sensing driven soft material composed of a thermoresponsive hydrogel poly(n-isopropylacrylamide) (PNIPAAm) and a light-absorbing conductive polymer polypyrrole (PPy). This design gives the material photo / thermal responsiveness and piezoresistive feedback, thereby achieving remote light-triggered actuation and local strain sensing. However, its sensing range is limited, and only significant resistance changes can be detected under tensile strains of >200% [Materials Today 2021, 11, 35-43].
[0004] In addition, some materials can sense the external environment and then control its actuation. Among them, contact sensing has been developed relatively maturely, and its sensing mechanisms include piezoelectric, piezoresistive, piezoceramic and triboelectric [Adv.Funct.Mater.2024,2401311]. Zhang et al. reported a single homogeneous material based on silver-polymer to simultaneously realize the sensing-driving function of pneumatic artificial muscles. The material senses and feedbacks contact mechanical signals based on capacitance and piezoresistive mechanisms, and can sense its own deformation [Adv.Mater.2023,35,2207916]. However, the demand for information exchange between humans and machines or virtual space is growing rapidly. Contact sensing cannot fully obtain environmental information, and it will inevitably cause mechanical wear and the spread of bacteria / viruses during the sensing process [Adv.Mater.2021,33,2100218]. Therefore, it is necessary to focus on the integration of non-contact sensing and actuation. According to the differences in the physical fields and detection mechanisms used, non-contact sensors can be roughly classified into various types, such as electric field, magnetic field, humidity field and light field [Sci.Adv.2022,8(43)]. For example, Ha et al. prepared a shape memory polymer composite film embedded with magnetic NdFeB particles, integrating photothermal and magnetic drive into an origami actuator, in which the laminated magnetic field sensor can guide self-assembly by detecting the magnetic field. However, the simple physical assembly of the actuator and the sensor element is prone to problems such as poor adhesion and mismatch of mechanical properties of different materials, and the entire system requires different energies for driving and sensing, making it difficult to miniaturize [Adv.Mater.2021,33,2008751]. Xue et al. proposed a multi-stimulus responsive actuator (MSRA) with an asymmetric expansion structure, and integrated arbitrary patterned carbon black / highly elastic transparent adhesive cement (CB / HETAC) conductive ink on the soft actuator by screen printing. MSRA not only bends in the opposite direction when driven by near-infrared light and humidity, but also has different bending angles and corresponding resistance feedback under a range of near-infrared light powers, enabling it to recognize its own deformation [ACS Appl. Polym. Mater. 2023, 5, 4525-4535]. In the work of non-contact sensing and actuation, most of the above devices perceive environmental information of special scenes, or are more reflected in the role of driving triggers such as light fields and magnetic fields, and do not perform logical perception of external field stimuli.
[0005] At present, there are problems in the design of integrated sensing-actuation materials, including: (1) When smart materials sense external environmental information, most of them stay at the contact or pressure sensing of the 2D skin surface, which leads to inevitable contact damage and power consumption, and transmits incomplete external environmental information; (2) When smart materials sense external non-contact stimuli, their non-contact information is mostly special environments, such as magnetic fields, humidity fields, light fields, etc., and the sensing function is single and cannot achieve logical perception of the direction and speed of movement of external objects; (3) In existing electrically / electrothermally driven flexible actuation materials, the driving voltage is large, such as tens or even hundreds of volts, which is not conducive to safe interaction and energy conservation and emission reduction. Summary of the invention
[0006] In view of the above technical problems, the present invention provides a non-contact sensing-actuating composite material and a preparation method thereof. The composite material provided by the present invention has a nano-scale multi-layer network structure, which is an intelligent material that integrates autonomous perception and actuation based on the triple effect of "dielectric polarization-electrothermal conversion-thermal response actuation". The composite material in the present invention can generate logical perception of the three-dimensional movement of non-contact objects in the environment based on the electrostatic field and its polarization effect on the dielectric material, establish a complete and accurate logical relationship with the three-dimensional movement and trigger the material to perform flexible actuation, thereby realizing non-contact "sensing-actuation" integration.
[0007] To achieve the above object, the technical solution adopted by the present invention is:
[0008] In one aspect, the present invention provides a method for preparing a non-contact sensing-actuating composite material, comprising the following steps:
[0009] S1. Pre-stretching the shape memory fiber membrane to produce deformation and then cooling and fixing it to obtain a sensing-actuating layer; the shape memory fiber membrane is a shape memory polyurethane fiber membrane doped with dielectric particles;
[0010] S2. Preparing electrodes on a portion of the upper surface of the sensing-actuating layer;
[0011] S3. Laminating the sensing-actuating layer on the incompletely cured polydimethylsiloxane (PDMS) film, and allowing the polydimethylsiloxane (PDMS) film to stand to completely cure; the surface of the sensing-actuating layer on which the electrodes are prepared faces the incompletely cured polydimethylsiloxane (PDMS) film;
[0012] S4. coating the silver nanowire dispersion on the surface of the sensing-actuating layer where no electrode is prepared, and obtaining the non-contact sensing-actuating composite material after drying.
[0013] In some specific embodiments, the thickness of the sensing-actuating layer is 40 to 90 μm; the thickness of the electrode is 30 to 80 μm; the thickness of the polydimethylsiloxane (PDMS) film after complete curing is 160 to 1750 μm; the thickness of the layer after the silver nanowire dispersion is coated and dried is 0.89 to 5.36 μm; in the technical solution of the present invention, the sensing-actuating layer of 40 to 90 μm can drive the bending actuation of the electrode, polydimethylsiloxane (PDMS) film and silver nanowire layer within the above thickness range.
[0014] As a preferred embodiment, in step S1, the soft segment in the shape memory polyurethane is selected from any one of polycaprolactone polyols; the polycaprolactone polyol is polycaprolactone diol (PCL-diol) or polycaprolactone triol (PCL-triol); the hard segment in the shape memory polyurethane is a product of a condensation reaction of a diisocyanate and 1,4-butanediol, and the diisocyanate is selected from any one of diphenylmethyl diisocyanate, hexamethylene diisocyanate and isophorone diisocyanate;
[0015] Preferably, the method for preparing the shape memory polyurethane comprises the following steps:
[0016] (1) prepolymerizing polycaprolactone polyol and diisocyanate;
[0017] (2) adding 1,4-butanediol and continuing the reaction;
[0018] Preferably, the mass ratio of the soft segment to the hard segment is 70-80:20-30, more preferably 72:28;
[0019] Preferably, the molar ratio of the total number of hydroxyl groups in the 1,4-butanediol and the polycaprolactone polyol to the isocyanate in the diisocyanate is 1:1 to 1.2, more preferably 1:1.05;
[0020] Preferably, the molecular weight of the polycaprolactone polyol is 3000 to 5000 g / mol;
[0021] Preferably, in step (1), the reaction temperature of the prepolymerization is 80 to 100° C., and the reaction time of the prepolymerization is 2 to 3 hours;
[0022] Preferably, in step (2), the temperature of the continued reaction is 80-100° C., and the time of the continued reaction is 0.5-5 min. In the technical solution of the present invention, a large amount of heat is released during the continued reaction.
[0023] Preferably, in step (1) and step (2), the prepolymerization and the continued reaction are carried out under stirring conditions;
[0024] In certain specific embodiments, step (2) further includes a vacuum degassing operation before adding 1,4-butanediol; step (2) also includes a post-treatment of drying, wherein the drying is performed at 80 to 100° C. for 8 to 12 hours;
[0025] In the technical solution of the present invention, 1,4-butanediol is used as a chain extender.
[0026] As a preferred embodiment, in step S1, the dielectric particles are boron nitride nanosheets;
[0027] Preferably, the boron nitride nanosheets are prepared by a liquid phase exfoliation method;
[0028] Preferably, the liquid phase exfoliation method comprises the following steps:
[0029] Dispersing boron nitride in a solvent and exfoliating the boron nitride nanosheets by ultrasonic oscillation;
[0030] In certain specific embodiments, the solvent is selected from any one of an aqueous solution of isopropanol, N-methylpyrrolidone and N,N-dimethylformamide; wherein the weight ratio of water to isopropanol in the aqueous solution of isopropanol is 1:1;
[0031] Preferably, the ultrasonic oscillation time is 6 to 12 hours;
[0032] In certain specific embodiments, the ultrasonic oscillation includes a post-treatment of collecting the supernatant by centrifugation and collecting the boron nitride nanosheet precipitate by centrifugation.
[0033] As a preferred embodiment, in step S1, the shape memory polyurethane fiber membrane is prepared by electrospinning a precursor solution containing boron nitride nanosheets and shape memory polyurethane;
[0034] Preferably, the solid content of the precursor solution containing boron nitride nanosheets and shape memory polyurethane is 5 to 15 wt %;
[0035] Preferably, in the precursor solution containing boron nitride nanosheets and shape memory polyurethane, the mass of the boron nitride nanosheets is 3% to 8% of the mass of the polyurethane;
[0036] Preferably, the solvent of the precursor solution is selected from any one of hexafluoroisopropanol, N,N-dimethylformamide, tetrahydrofuran, dichloromethane and chloroform;
[0037] In certain specific embodiments, the method for preparing the precursor solution containing boron nitride nanosheets and shape memory polyurethane comprises the following steps: dissolving the shape memory polyurethane in a solvent, adding the boron nitride nanosheets and dispersing them uniformly; wherein the shape memory polyurethane is dissolved in the solvent under heating conditions, and the heating temperature is 45 to 60° C.;
[0038] Preferably, the ambient temperature of the electrospinning is 45-60°C;
[0039] Preferably, in the electrospinning, the distance between the nozzle and the collector is 10 to 20 cm;
[0040] Preferably, the collector is a rotary collector, and the rotation speed of the rotary collector is 1000-5000 rpm;
[0041] As a preferred embodiment, the pre-stretching produces deformation to a strain of 100 to 300%;
[0042] Preferably, the pre-stretching is carried out at 35-80°C:
[0043] Preferably, the cooling and fixing temperature is 0-15°C.
[0044] In the technical solution of the present invention, in step S2, the material of the electrode layer is not particularly limited, and any metal with good conductivity can be used, such as copper, silver, etc.
[0045] As a preferred embodiment, in step S3, the method for preparing the incompletely cured polydimethylsiloxane (PDMS) film comprises the following steps:
[0046] Mix the polydimethylsiloxane and the curing agent and pre-cure at 80-120°C for 3-5 minutes;
[0047] In the technical solution of the present invention, the curing agent is a conventional curing agent used for curing polydimethylsiloxane;
[0048] Preferably, in step S3, the mass ratio of the polydimethylsiloxane to the curing agent is 10 to 15:1;
[0049] Preferably, in step S3, the standing time in the standing is 8 to 24 hours;
[0050] In the technical solution of the present invention, during the static process, the incompletely cured polydimethylsiloxane can slightly penetrate the contact surface of the sensing-actuating layer through diffusion.
[0051] As a preferred embodiment, in step S4, the silver nanowire dispersion comprises silver nanowires and a dispersant; the diameter of the silver nanowires is 30 to 90 nm and the length is 2 to 20 μm; the dispersant is selected from at least one of water, isopropanol, ethanol, cyclohexane and glycerol; the concentration of the silver nanowire dispersion is 0.1 to 100 mg / mL;
[0052] In the technical solution of the present invention, when the coating amount of the silver nanowire dispersion is different, it has different resistance after drying, and generates different heat when powered on. By controlling its resistance, the optimal thermal response drive of the sensing-actuating layer can be achieved;
[0053] Preferably, in step S4, the drying is air-drying at room temperature;
[0054] In some specific embodiments, the coating further includes a step of plasma treating the sensing-actuating layer and the sensing-actuating layer in the polydimethylsiloxane (PDMS) film after standing. After the plasma treatment, the silver nanowire dispersion can be evenly spread on the sensing-actuating layer.
[0055] In another aspect, the present invention provides a non-contact sensing-actuating composite material obtained by the above preparation method.
[0056] In the technical solution of the present invention, the non-contact sensing-actuating composite material comprises a silver nanowire layer, a sensing-actuating layer, an electrode and a polydimethylsiloxane-based bottom layer in sequence; the silver nanowire layer is formed by drying a silver nanowire dispersion; the two ends of the silver nanowire layer in the non-contact sensing-actuating composite material are connected by wires, respectively, and the composite material can realize actuation behavior under electrothermal drive; the electrodes are connected by wires, and the composite material can realize non-contact "dielectric polarization-electrothermal conversion-thermal response actuation" integration.
[0057] The above technical solution has the following advantages or beneficial effects:
[0058] The present invention provides a non-contact sensing-actuating composite material based on dielectric and shape memory polymer. The composite material provided by the present invention is based on a thermal response shape memory polymer network, coupled with a dielectric / thermal network formed by dielectric particles such as boron nitride (BNNS), and a silver nanowire electrothermal conversion network. Based on the regulation of the dielectric constant, the conductive-dielectric heterostructure can realize the material's logical perception of the movement of external objects (including movement direction, speed, distance, etc.), and establish an accurate logical relationship with the three-dimensional movement of the object through the positive / negative, frequency and amplitude of the sensing signal, and its sensing distance can reach 20cm; further, the composite material loads the output voltage of the non-contact sensing signal on the silver nanowire layer with electrothermal effect, and drives the shape memory polymer to generate action feedback by regulating the resistance of the silver nanowire layer. The thermal response actuation time is less than 1s, and its shape memory recovery rate is greater than 95%.
[0059] The composite material provided by the present invention can realize the integration of "sensing-actuation" based on the triple effect coupling of "dielectric polarization-electrothermal conversion-thermal response actuation". The material can trigger the flexible actuation through the logical perception of the three-dimensional movement of the external non-contact object, specifically, the non-contact sensing based on the electrostatic field theory is realized through the dielectric properties of the material, and the logical electrical signal is output; the signal and energy conversion of the electrothermal network drives the thermal response polymer network to realize flexible actuation, which is consistent with the sensing function. The preparation method and process of the non-contact "sensing-actuation" polymer composite material are simple, easy to implement in industrialization, and have wide applicability.
[0060] Compared with the prior art, the present invention has the following advantages:
[0061] (1) The sensing function and actuation function of traditional smart materials are independent and separate, and sensing and actuation require different energies. The present invention integrates the sensing layer and the actuation layer in the same material at the nano level. The structure is simple, and sensing and actuation can be achieved using a single energy conversion.
[0062] (2) The preparation process of the present invention is simple, and the obtained composite material has both actuation ability and sensing stability; traditional flexible actuation materials not only require voltage drive, but also have harsh driving conditions and require a relatively high driving voltage; the driving voltage of the composite material provided by the present invention is as low as 2V, and the response speed is within 1s, which lowers the threshold for use.
[0063] (3) Most of the current non-contact sensing materials require special environmental excitation, such as magnetic field, humidity field, light field, etc., and the sensing function is single and cannot realize the logical perception of the non-contact movement of ordinary objects in daily scenes. The non-contact sensing mechanism in the present invention utilizes the polarization effect of electrostatic field on dielectric materials, has no special scene restrictions, and expands the scope of application. BRIEF DESCRIPTION OF THE DRAWINGS
[0064] Figure 1 This is a scanning electron microscope (SEM) result of the shape memory polyurethane fiber membrane in Example 1 of the present invention.
[0065] Figure 2 This is a differential scanning calorimetry (DSC) result diagram of the shape memory polyurethane fiber membrane with different BNNS doping amounts in Example 1 of the present invention.
[0066] Figure 3 This is a graph showing the dielectric constant test results of shape memory polyurethane fiber membranes with different BNNS doping amounts in Example 1 of the present invention.
[0067] Figure 4 This is a non-contact sensing signal diagram of the shape memory polyurethane fiber membrane with different BNNS doping amounts in Example 1 of the present invention.
[0068] Figure 5 This is a diagram of the thermal response bending actuation process of the BNNS / SMPUFs-PDMS composite film in Example 2 of the present invention.
[0069] Figure 6 This is a time-electrothermal temperature curve of the AgNWs layer with different resistances of the film-like composite material AgNWs-BNNS / SMPUFs-PDMS in Example 2 of the present invention at a voltage of 2V.
[0070] Figure 7 This is the electrothermal response bending actuation diagram of the film-like composite material AgNWs-BNNS / SMPUFs-PDMS in Example 2 of the present invention.
[0071] Figure 8 These are the test results of the induced electromotive force generated by the film-like composite material AgNWs-BNNS / SMPUFs-PDMS in Example 2 of the present invention when a charged object moves toward or away from it.
[0072] Fig. 9 Schematic diagram of connecting the film-like composite material AgNWs-BNNS / SMPUFs-PDMS in Example 2 of the present invention with conductive copper wires.
[0073] Fig.10 This is the non-contact sensing-actuating fusion roadmap of the film-like composite material AgNWs-BNNS / SMPUFs-PDMS in Example 3 of the present invention. DETAILED DESCRIPTION
[0074] The following embodiments are only some embodiments of the present invention, rather than all embodiments. Therefore, the detailed description in the embodiments of the present invention provided below is not intended to limit the scope of the present invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work belong to the protection scope of the present invention.
[0075] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.
[0076] In the following embodiments:
[0077] The molecular weight of polycaprolactone diol (PCL-diol) is M n =4000 g·mol -1 ;
[0078] The molecular weight of diphenylmethane diisocyanate (MDI) is M n =250.26 g·mol -1 ;
[0079] The molecular weight of 1,4-butanediol (BDO) is M n =90.12 g·mol -1 ;
[0080] The size of the boron nitride nanosheets is 200 nm.
[0081] Example 1 Preparation of shape memory polyurethane fiber membrane (BNNS / SMPUFs)
[0082] (1) Synthetic shape memory polyurethane (SMPU)
[0083] With PCL-diol as the soft segment and MDI-BDO as the hard segment, SMPU with a soft segment and hard segment mass ratio of 72 / 28 was synthesized, wherein the molar ratio of hydroxyl group to isocyanate group was 1:1.05. The specific synthesis route is as follows:
[0084] PCL-diol and BDO were vacuum dried for 2 hours; 25g PCL-diol and 7.65g MDI were stirred in a three-necked flask at 85°C for prepolymerization for 2 hours; bubbles were removed by vacuum, and then 2.06g BDO was added dropwise for chain extension. When a large amount of heat was released, it was quickly poured into a polytetrafluoroethylene plate mold and placed in an oven at 80°C for 12 hours to obtain shape memory polyurethane SMPU;
[0085] (2) Preparation of Boron Nitride Nanosheets (BNNS) by Liquid Phase Exfoliation
[0086] 3.5 g of BN was dispersed in 200 mL of a mixed solvent of deionized water and isopropanol (the weight ratio of deionized water to isopropanol was 1:1) and subjected to ultrasonic peeling for 8 h. The agglomerates were then removed by centrifugation at 2000 rpm for 5 min, and the supernatant was collected. The supernatant was then centrifuged at 10000 rpm for 30 min, and the precipitate on the tube wall was collected to obtain boron nitride nanosheets (BNNS).
[0087] (3) Preparation of shape memory polyurethane fiber membranes (BNNS / SMPUFs)
[0088] The SMPU synthesized in step (1) was dissolved in hexafluoroisopropanol at 45°C for 2h, and BNNS was added according to the amount in Table 1 and magnetically stirred for 1h. The obtained BNNS / SMPU precursor solution was sucked into a syringe and placed in a 35kV voltage environment for electrospinning at a propulsion speed of 2mL / h for 6h, wherein the spinneret was at a positive pressure of 25kV, the receiving drum was at a negative pressure of 10kV, the spinning environment temperature was 45°C, the distance between the needle and the drum surface was 15cm, and the nanofibers were collected on a drum covered with aluminum foil at a rotation speed of 3000rpm. After the spinning was completed, the fiber membrane was peeled off from the aluminum foil to obtain a shape memory polyurethane fiber membrane (BNNS / SMPUFs).
[0089] Table 1
[0090]
[0091] In Table 1, the doping amount of BNNS is the mass ratio of BNNS in SMPU.
[0092] Figure 1 Shown are scanning electron microscope (SEM) images of the shape memory polyurethane fiber membrane samples 1-4 prepared as described above. It can be seen from the images that the membrane has a directionally extended fiber structure.
[0093] Figure 2 The figure shows the test results of differential scanning calorimetry (DSC) of the shape memory polyurethane fiber membrane samples 1-4 prepared as described above. It can be seen that the melting temperature range of the shape memory polyurethane fiber membrane is 20 to 50°C.
[0094] Figure 3 Shown is the dielectric constant test results of the shape memory polyurethane fiber membrane samples 1-4 prepared above with different boron nitride nanosheet doping amounts. It can be seen from the figure that with the increase of the boron nitride nanosheet content, the dielectric constant gradually increases, and the dielectric constants of all samples decrease with increasing frequency and tend to be stable at high frequencies.
[0095] Figure 4Shown is a test diagram of the non-contact sensing signal results of the shape memory polyurethane fiber membrane samples 1-4 prepared as described above, which was tested by an Agilent multimeter (model 34411A). It can be seen from the figure that the non-contact sensing voltage signal of composite membrane sample 4 is the highest.
[0096] Example 2 Preparation of film-like composite material AgNWs-BNNS / SMPUFs-PDMS
[0097] (1) The shape memory polyurethane fiber membrane sample 4 prepared in Example 1 was pre-stretched to a strain of 100% at 50° C., and the deformation was fixed at a low temperature of 15° C., thereby completing pre-programming and fixing;
[0098] (2) Polydimethylsiloxane (PDMS) and curing agent (PDMS184 curing agent) were mixed evenly at a weight ratio of 10:1, spread on a glass plate, and placed in an oven at 80°C for 4 minutes to form a semi-cured state;
[0099] (3) attaching a copper foil frame with a thickness of 60 μm to the shape memory polyurethane fiber membrane fixed in step (1), wherein the shape and size of the copper foil frame are consistent with the shape memory polyurethane fiber membrane, but the copper foil frame is a frame structure containing only four sides, and the width of the four sides is 1 / 8 of the width of the shape memory polyurethane fiber membrane;
[0100] (4) The shape memory polyurethane fiber membrane was laminated on the upper layer of the semi-cured PDMS membrane, with the copper foil attached to the surface of the shape memory polyurethane fiber membrane facing the PDMS membrane, and placed at room temperature for 12 hours; during the placement, the PDMS was completely cured and slightly penetrated the shape memory polyurethane fiber membrane by diffusion, and finally formed a strong BNNS / SMPUFs-PDMS composite membrane; wherein the thickness of the shape memory polyurethane fiber membrane was 60 μm, and the thickness of the PDMS membrane was 1 mm;
[0101] (5) Plasma surface treatment was performed on the BNNS / SMPUFs of the BNNS / SMPUFs-PDMS composite membrane for 5 min, and 5 mol / L of silver nanowires (AgNWs, 90 nm in diameter, 5 μm in length) aqueous dispersion was droplet-coated and spread on the BNNS / SMPUFs of the BNNS / SMPUFs-PDMS composite membrane according to the dosage in Table 2 and infiltrated; if the spreading was uneven during this process, it could be solved by plasma treatment for 5 min;
[0102] (6) After air drying at room temperature, the final film-like composite material AgNWs-BNNS / SMPUFs-PDMS was obtained, in which the layer formed after the silver nanowire aqueous dispersion was dried was named AgNWs layer.
[0103] Table 2
[0104]
[0105] Use conductive copper wire to connect the two ends of the AgNWs layer in the film-like composite AgNWs-BNNS / SMPUFs-PDMS in Examples 2.0 to 2.3 (such as Fig. 9 As shown), and a voltage of 2 V was applied, it was observed that the composite film produced bending actuation driven by the electrothermal effect of the AgNWs layer network.
[0106] The thermal response actuation results of the BNNS / SMPUFs-PDMS composite membrane obtained in step (4) are shown in Figure 5 ,from Figure 5 It can be seen from the figure that the composite film can respond within the melting temperature range. The higher the temperature, the greater the bending actuation angle of the composite film (the bending actuation angle is the angle of the arc formed at both ends of the sample, such as Figure 5 As shown in the figure below, when the temperature is higher than 45°C, the bending actuation angle no longer increases.
[0107] The time-electrical temperature curves of the AgNWs layers with different resistances of the film-like composite material AgNWs-BNNS / SMPUFs-PDMS at a voltage of 2 V are shown in FIG. Figure 6 , the resistance values in the figure correspond to Table 2. It can be seen from the figure that when a constant voltage of 2V is applied, the temperature generated by the electric heating of Examples 2.0 to 2.2 is lower than 50°C, failing to reach the minimum temperature (45°C) required for the maximum bending actuation angle of the composite film, while the temperature generated by the electric heating of Example S3 is as high as 53°C, which can reach the temperature required for the maximum bending actuation angle of the composite film.
[0108] The results of the bending actuation produced by the electrothermal response of the film-like composite material AgNWs-BNNS / SMPUFs-PDMS in this example are shown in Figure 7 , it can be seen that after applying electrothermal stimulation to Example 2.3, the composite film can respond in real time, and the bending actuation angle increases with the increase of temperature.
[0109] The film-like composite material AgNWs-BNNS / SMPUFs-PDMS in this embodiment can respond to actuation in real time under the action of electrothermal effect and thermal response effect when powered on (only electrical stimulation is applied). The test results of the film-like composite material AgNWs-BNNS / SMPUFs-PDMS in Example 2.3 on the induced electromotive force generated by the approach-away movement of a naturally charged object are shown in Figure 8 From the figure, we can see that the composite film can sense the approach and distance of objects, and there is a continuous sensing signal while maintaining a close distance. The response time of the approach process is 250ms, and the recovery time of the distance process is 250ms. Figure 8The specific test process is as follows: the positive electrode of the Agilent multimeter is connected to the copper foil with a copper wire, and the negative electrode is suspended in the air as a reference electrode. The initial position of the external charged object PTFE is 20 cm away from the surface of the film composite material AgNWs-BNNS / SMPUFs-PDMS. During the approaching movement, the PTFE approaches the material surface in the vertical direction until the vertical distance is 3 cm. The movement process of moving away is opposite to that of approaching, specifically returning to the initial point along the opposite trajectory. The composite material sensed output electromotive force of the PTFE "approach-away" movement process is measured by a multimeter.
[0110] Example 3 Preparation of non-contact sensor-actuator
[0111] The process and principle of preparing non-contact sensor-actuator are as follows Fig.10 As shown, build the circuit (such as Fig. 9 As shown in the figure, the Agilent multimeter is used to collect and record the material sensing signals in real time; secondly, the collected signals are transmitted via USB and converted into digital signals, and then outputted back to the material heating layer through the HLR-3003 programmable linear DC power supply to drive the material to actuate, thus completing the non-contact "sensing-actuation" circuit.
[0112] In the present invention, when an external charged object approaches the film-like composite material AgNWs-BNNS / SMPUFs-PDMS, due to the dielectric properties of the "sensing-actuating" layer therein, a polarization response is generated to the external charged object, which is manifested as the local movement of the internal charge of the layer under the action of polarization, generating an electromotive force signal, and further outputting the non-contact sensing electrical signal and returning it to the material itself. The system temperature is increased through the electrothermal effect of the AgNWs layer, and the material is driven to generate thermal response actuation, thereby realizing the fusion of non-contact "sensing-actuating" and preparing a non-contact sensor-actuator.
[0113] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a non-contact sensing-actuating composite material, characterized in that: The following steps are involved: S1. Pre-stretching the shape memory fiber membrane to produce deformation and then cooling and fixing it to obtain a sensing-actuating layer; the shape memory fiber membrane is a shape memory polyurethane fiber membrane doped with dielectric particles; S2. Preparing electrodes in a partial area of the upper surface of the sensing-actuating layer; S3. Laminating the sensing-actuating layer on the uncured polydimethylsiloxane film and allowing the polydimethylsiloxane film to stand until it is completely cured; The surface of the sensing-actuating layer on which the electrodes are prepared faces the uncured polydimethylsiloxane film; S4. coating the silver nanowire dispersion on the surface of the sensing-actuating layer where no electrode is prepared, and obtaining the non-contact sensing-actuating composite material after drying.
2. The preparation method according to claim 1, characterized in that: In step S1, the soft segment in the shape memory polyurethane is selected from any one of polycaprolactone polyols; the polycaprolactone polyol is polycaprolactone diol or polycaprolactone triol; the hard segment in the shape memory polyurethane is a product of a condensation reaction of a diisocyanate and 1,4-butanediol, and the diisocyanate is selected from any one of diphenylmethyl diisocyanate, hexamethylene diisocyanate and isophorone diisocyanate.
3. The preparation method according to claim 2, characterized in that: The preparation method of the shape memory polyurethane comprises the following steps: (1) prepolymerizing polycaprolactone polyol and diisocyanate; (2) adding 1,4-butanediol and continuing the reaction; Preferably, the mass ratio of the soft segment to the hard segment is 70-80:20-30, more preferably 72:28; Preferably, the molar ratio of the total number of hydroxyl groups in the 1,4-butanediol and the polycaprolactone polyol to the isocyanate in the diisocyanate is 1:1 to 1.2, more preferably 1:1.05; Preferably, the molecular weight of the polycaprolactone polyol is 3000 to 5000 g / mol; Preferably, in step (1), the reaction temperature of the prepolymerization is 80 to 100° C., and the reaction time of the prepolymerization is 2 to 3 hours; Preferably, in step (2), the temperature of the continued reaction is 80-100° C., and the time of the continued reaction is 0.5-5 min.
4. The preparation method according to claim 1, characterized in that: In step S1, the dielectric particles are boron nitride nanosheets; Preferably, the boron nitride nanosheets are prepared by a liquid phase exfoliation method.
5. The preparation method according to claim 4, characterized in that: The liquid phase exfoliation method comprises the following steps: dispersing boron nitride in a solvent, and exfoliating by ultrasonic oscillation to obtain the boron nitride nanosheets; Preferably, the ultrasonic oscillation time is 6 to 12 hours.
6. The preparation method according to claim 1, characterized in that: In step S1, the shape memory polyurethane fiber membrane is prepared by electrospinning a precursor solution containing boron nitride nanosheets and shape memory polyurethane; Preferably, the solid content of the precursor solution containing boron nitride nanosheets and shape memory polyurethane is 5 to 15 wt %; Preferably, in the precursor solution containing boron nitride nanosheets and shape memory polyurethane, the mass of the boron nitride nanosheets is 3% to 8% of the mass of the polyurethane; Preferably, the solvent of the precursor solution is selected from any one of hexafluoroisopropanol, N,N-dimethylformamide, tetrahydrofuran, dichloromethane and chloroform; Preferably, the ambient temperature of the electrospinning is 45-60°C; Preferably, in the electrospinning, the distance between the nozzle and the collector is 10 to 20 cm; Preferably, the collector is a rotary collector, and the rotation speed of the rotary collector is 1000-5000 rpm.
7. The preparation method according to claim 1, characterized in that: In step S1, the pre-stretching produces deformation to a strain of 100 to 300%; Preferably, the pre-stretching is carried out at 35-80°C: Preferably, the cooling and fixing temperature is 0-15°C.
8. The preparation method according to claim 1, characterized in that: In step S3, the method for preparing the incompletely cured polydimethylsiloxane film comprises the following steps: Mix the polydimethylsiloxane and the curing agent and pre-cure at 80-120°C for 3-5 minutes; Preferably, in step S3, the standing time is 8 to 24 hours.
9. The preparation method according to claim 1, characterized in that: In step S4, the silver nanowire dispersion comprises silver nanowires and a dispersant; the diameter of the silver nanowires is 30 to 90 nm and the length is 2 to 20 μm; the dispersant is selected from at least one of water, isopropanol, ethanol, cyclohexane and glycerol; the concentration of the silver nanowire dispersion is 0.1 to 100 mg / mL; Preferably, in step S4, the drying is air-drying at room temperature.
10. The non-contact sensing-actuating composite material obtained by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Flexible capacitive sensor based on silver nanowire material and preparation method thereof
CN112985470A
Shape memory polyurethane material with active oxygen responsiveness and anti-adhesion double functions
CN113845643A
Flexible stretchable hardness sensor based on polydimethylsiloxane and preparation method thereof
CN114062168A
Three-dimensional depth-of-field touch sensor and preparation method and application thereof
CN114705225A
Polymer-based biomedical scaffold and preparation method thereof
CN116196485A